An experimental research on emotional stimuli of consumers: The case of H&M flagship store on the millennial customer experience in Barcelona - Elisa Regadera González; Rejina M. Selvam; Irene García Medina; Zahaira Fabiola González Romo (Intangible Capital, 2022)
Purpose: The main objective of this exploratory research study was to demonstrate the extent to which customers' approach-avoidance responses to fast fashion flagship stores can be predicted from their emotional states framed according to the PAD (Pleasure, Arousal, and Dominance) model and information rates. Design/methodology/approach: Data was collected through a survey questionnaire from 72 randomly selected millennials visiting H&M flagship store, just after their visit (55% women and 45% men). Data was analysed using exploratory factor analysis to classify the measures and later through regression analysis explaining the predictor variables. Findings: In accordance with the theory and past research on PAD measures, results show PAD as a highly predictable variable over most of the approach-avoidance behaviour in a flagship store environment. Pleasure variable shows highly significant relationship with affect, approach-avoidance (average of all measures of approach-avoidance), and time spent in the store and to an extent significantly relates to purchase intentions. This signifies that in a highly pleasant environment, an individual’s affectionate behaviour, to remain exploring in the store for a longer time, and on an average the approach behaviour to the flagship store will be highly positive. Originality/value: This study is a unique exploration, as very little is known in the literature, on flagship store influences over consumer experiences. Findings suggest interesting advancement in the field of in person shopping effects and encourages future research in flagship store economic investments and marketing impacts, which may extend consumer behavioural scopes as well. This exploratory research may have implications of interest for business strategic decision, brand management, and for marketing as well. As brands seek to recover consumers in their physical stores, offering them a safer and more complete shopping experience, flagship stores can play a key role in encouraging online customers’ visiting stores in-person, which may ultimately increase sales.